Pemantauan Status Gizi dan Deteksi Dini Kekurangan Energi Kronis (KEK) serta Pemberian Edukasi Kesehatan secara Holistik dalam Upaya Peningkatan Kesehatan Reproduksi pada Remaja Putri di SMP YPI Ciparay Kabupaten Bandung - Meita Dhamayanti; Veranita Pandia; Nita Arisanti; Devi Azriani; Lusiana El Sinta Bustami; Hesty Widyasih; Made Yos Kresnayana (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2023)
From 10–19, adolescence is a transition from childhood to adulthood. There will be changes in the shape and function of the body in a reasonably short time. Sufficient and adequate nutrition for adolescents is one factor affecting their reproductive health. This community service aimed to monitor nutritional status and detect early signs of Chronic Energy Deficiency (CED). Monitoring of nutritional status is carried out for adolescents, especially young women. Physical health and healthy reproductive organs are essential in preparation for becoming healthy expectant mothers who can later give birth to a healthy generation. Holistic health education was needed in adolescents' growth to become better human beings in terms of their health. This activity was carried out in May 2023 at Junior High School, YPI Ciparay, and Bandung Regency. The target audience was young girls in 7th grade; there were 82 people. At the time, the students filled out questionnaires about their characteristics. Then the team measured the anthropometrics to determine the nutritional status and the incidence of CED by weighing, measuring height, and measuring upper arm circumference. The measurements showed that the nutritional status based on body mass index for most female students was standard, about 60.97%, and 41.46% of female students were CED. Counselling and health information were also provided holistically to increase the girls' understanding of their health status.